2009
DOI: 10.1038/jcbfm.2009.241
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal in vivo Imaging Reveals Balanced and Branch-Specific Remodeling of Mature Cortical Pyramidal Dendritic Arbors after Stroke

Abstract: The manner in which fully mature peri-infarct cortical dendritic arbors remodel after stroke, and thus may possibly contribute to stroke-induced changes in cortical receptive fields, is unknown. In this study, we used longitudinal in vivo two-photon imaging to investigate the extent to which brain ischemia can trigger dendritic remodeling of pyramidal neurons in the adult mouse somatosensory cortex, and to determine the nature by which remodeling proceeds over time and space. Before the induction of stroke, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 42 publications
2
89
1
1
Order By: Relevance
“…However, our findings differ significantly from a recent in vivo two-photon microscopy study that examined the length and branching of pyramidal dendrites in peri-infarct cortex (Brown et al, 2010). The authors followed cortical pyramidal cells for up to 6 weeks after a photo-thrombotic stroke, which produces relatively tiny and well-circumscribed infarcts.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, our findings differ significantly from a recent in vivo two-photon microscopy study that examined the length and branching of pyramidal dendrites in peri-infarct cortex (Brown et al, 2010). The authors followed cortical pyramidal cells for up to 6 weeks after a photo-thrombotic stroke, which produces relatively tiny and well-circumscribed infarcts.…”
Section: Discussioncontrasting
confidence: 56%
“…This was somewhat surprising as we expected that dendrites closer to the infarct edge, because they were exposed to more ischemia, might suffer more retractions, as reported previously (Brown et al, 2010). The difference may reside in the fact that we sampled dendrites significantly farther away from the infarct edge.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This can be seen also as supernumerary axons exiting the neuronal cell body [66]. The actual branches of dendrites also remodel after stroke, with retraction and growth that is maximal 2 weeks after the infarct and occurs most prominently within 200 μm of the infarct core [67]. Stroke also induces new axonal connections from neurons in peri-infarct cortex, which are initiated in the first week after stroke and are reliably present 1 month after stroke [39,68,69], particularly in the superficial cortical layers.…”
Section: Radial Stroke: Tissue Reorganizationmentioning
confidence: 99%
“…Whereas extensive literature has shown that rehabilitation can increase the numbers of dendritic spines and dendritic complexity in the cortical hemisphere opposite a brain lesion (10)(11)(12)(13) and is associated with improved skill in the limb unaffected by the lesion, effects of rehabilitation on neuronal structure in perilesioned cortex have not been described. Indeed, some studies suggest either stability or early loss of dendritic structure in perilesion cortex (14)(15)(16). However, knowing whether rehabilitation can drive adaptive brain plasticity could be essential in improving outcomes of numerous CNS disorders acquired in adulthood, including stroke, traumatic brain injury, and spinal cord injury.…”
mentioning
confidence: 99%